Abscisic Acid and LATERAL ROOT ORGAN DEFECTIVE/NUMEROUS INFECTIONS AND POLYPHENOLICS Modulate Root Elongation via Reactive Oxygen Species in Medicago truncatula . Issue 2 (5th September 2014) - Zhang, Chang; Bousquet, Amanda; Harris, Jeanne M.
Abstract : Both abscisic acid and a nitrate transporter regulate the production of ROS and the expression of superoxide-generating NADPH oxidase enzymes to regulate root elongation . Abstract: Abscisic acid (ABA ) modulates root growth in plants grown under normal and stress conditions and can rescue the root growth defects of the Medicago truncatula lateral root-organ defective ( latd ) mutant. Here, we demonstrate that reactive oxygen species (ROS ) function downstream of ABA in the regulation of root growth by controlling cell elongation. We also show that the MtLATD/NUMEROUS INFECTIONS AND POLYPHENOLICS (NIP) nitrate transporter is required for ROS homeostasis and cell elongation in roots and that this balance is perturbed in latd mutants, leading to an excess of superoxide and hydrogen peroxide and a corresponding decrease in cell elongation. We found that expression of the superoxide-generating NADPH oxidase genes, MtRbohA and MtRbohC (for respiratory burst oxidase homologs), is increased in latd roots and that inhibition of NADPH oxidase activity pharmacologically can both reduce latd root ROS levels and increase cell length, implicating NADPH oxidase function in latd root growth defects. Finally, we demonstrate that ABA treatment alleviates ectopic ROS accumulation in latd roots, restores MtRbohC expression to wild-type levels, and promotes an increase in cell length. Reducing the expression of MtRbohC using RNA interference leads to increased root elongation in both wild-type and latd roots. These results reveal a mechanism by which the MtLATD/NIP nitrate transporter and ABA modulate root elongation via superoxide generation by the MtRbohC NADPH oxidase.